Seeking and sharing: why the pulmonary fibrosis community engages the web 2.0 environment. Issue 1 (December 2016) - Albright, Karen; Walker, Tarik; Baird, Susan; Eres, Linda; Farnsworth, Tara; Fier, Kaitlin; Kervitsky, Dolly; Korn, Marjorie; Lederer, David; McCormick, Mark; Steiner, John; Vierzba, Thomas; et al.
Abstract Background Pulmonary fibrosis (PF) is a rare, progressive disease that affects patients and their loved ones on many levels. We sought to better understand the needs and interests of PF patients and their loved ones (collectively "reader-participants") by systematically analyzing their engagement with the World Wide Web (the current version referred to as Web 2.0). Methods Data were collected from three PF-focused, interactive websites hosted by physician-investigators with expertise in PF. All data generated by reader-participants for approximately 10 months were downloaded and then analyzed using qualitative content analysis methods. Results PF experts posted 38 blog entries and reader-participants posted 40 forum entries. Blogs received 363 responses, and forum entries received 108 responses from reader-participants. Reader-participants primarily used the three websites to seek information from or offer a contribution to the PF community. Information was sought about PF symptoms, diagnosis, prognosis, treatments, research, pathophysiology, and disease origin; reader-participants also made requests for new posts and pleas for research and sought clarification on existing content. Contributions included personal narratives about experiences with PF, descriptions of activities or behaviors found to be helpful with PF symptoms, resources or information about PF, and supportive comments to other PF sufferers. Conclusions PF patients and their loved ones engage the Web 2.0 environment at these PF-focused sites to satisfy their needs to better understand PF and its impacts and to support others facing similar challenges. Clinicians may find it beneficial to encourage PF patients' involvement in internet forums that foster dynamic, bi-directional information sharing.